2009
DOI: 10.1002/bies.200800163
|View full text |Cite
|
Sign up to set email alerts
|

Important roles for epithelial cell peptides in hydra development

Abstract: It has been convincingly shown that peptides play important roles in the regulation and maintenance of a variety of tissues and organs in living animals. However, little is known concerning the potential role of peptides as signaling molecules in developmental processes. In Hydra, there is circumstantial evidence that small diffusible molecules act as morphogens in the regulation of patterning processes. In order to view the entire spectrum of peptide signaling molecules, we initiated a project aiming at the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…1B) by the expression boundaries of Gata, Hym323 and Cnox1 (Gauchat et al, 2000;Takahashi et al, 2005;Takahashi and Fujisawa 2009;Nakamura et al, 2011). This diffuse boundary zone seems to correlate with the lower end of the proliferation zone.…”
Section: Lower Body Regionmentioning
confidence: 87%
“…1B) by the expression boundaries of Gata, Hym323 and Cnox1 (Gauchat et al, 2000;Takahashi et al, 2005;Takahashi and Fujisawa 2009;Nakamura et al, 2011). This diffuse boundary zone seems to correlate with the lower end of the proliferation zone.…”
Section: Lower Body Regionmentioning
confidence: 87%
“…This led to the biochemical isolation of an 11 amino acid peptide, called the head activator (Schaller and Gierer 1973 ), which indeed had reproducible, although subtle, effects on head regeneration and on proliferation (Schaller et al 1990 ;Hobmayer et al 1997 ). However, a large-scale biochemical approach to isolate as many peptides as possible could not recover the head activator (Takahashi and Fujisawa 2009 ;Takahashi 2013 ), nor could it later be found in the genome sequence . It is therefore unclear whether the head activator peptide has still been missed -despite considerable depth of sequencing and screening efforts -or whether it does not exist and the biological effects simply mimic the effect of a related endogenous peptide, since many of them have clear effects on morphogenesis and cellular differentiation (Takahashi and Fujisawa 2009 ;Takahashi 2013 ).…”
Section: The Head Organizer and Axis Formationmentioning
confidence: 97%
“…However, a large-scale biochemical approach to isolate as many peptides as possible could not recover the head activator (Takahashi and Fujisawa 2009 ;Takahashi 2013 ), nor could it later be found in the genome sequence . It is therefore unclear whether the head activator peptide has still been missed -despite considerable depth of sequencing and screening efforts -or whether it does not exist and the biological effects simply mimic the effect of a related endogenous peptide, since many of them have clear effects on morphogenesis and cellular differentiation (Takahashi and Fujisawa 2009 ;Takahashi 2013 ). Other molecules that have an effect on the headforming capacity of body column tissue are diacylglycerol (DAG) and lithium ions (Muller 1990 ;Hassel et al 1993 ;Hassel and Bieller 1996 ).…”
Section: The Head Organizer and Axis Formationmentioning
confidence: 97%
“…In the case of Trichoplax, a bifunctional PAM and cells that react to an antibody against the amidated peptide RFamide (which in the closely related cnidarians acts as an important neurotransmitter) are present (Schuchert 1993), consistent with the idea that Trichoplax is secondarily simplified from a more complex ancestor Srivastava et al 2008) that perhaps used amidated peptides for signaling. Recent work Attenborough et al · doi:10.1093/molbev/mss114 MBE on Hydra (Takahashi and Fujisawa 2009), where peptides secreted by epithelial cells have been implicated as short range signaling molecules involved in pattern formation, suggests a possible role for PAM in sponges. These same authors quote unpublished work indicating that PHM and PAL are found in choanocytes and archeocytes of the freshwater sponge Ephydatia fluviatilis and speculate that an early role of amidated peptides may have been interepithelial cell communication.…”
Section: Discussionmentioning
confidence: 99%